CERAMICS FROM THE IRGANAYSKAYA SETTLEMENT I BASED ON MATERIALS OF THE RESEARCH IN 2005 - Sajpudinov, M S (History, Archeology and Ethnography of the Caucasus, 2016)
The article discusses the ceramic Irganayskaya settlement I -era average , and the early stage of the Late Bronze Age , revealed as a result of research in the area of ​​construction of Irganayskaya Hydroelectric power station. The analysis of the ceramic complexes of the settlement based on expeditions 2005. Count the number of members of ceramic complexes are described patterns, a comparative analysis of the ceramic material and the classification of the forms and types of vessels
Keywords: the Middle Bronze Age; mountain Dagestan Irganay; settlement; pottery; typology; classification; ornamentation